Streptococcus agalactiae Infects Glial Cells and Invades the Central Nervous System via the Olfactory and Trigeminal Nerves - Chacko, Anu; Delbaz, Ali; Choudhury, Indra N.; Eindorf, Tanja; Shah, Megha; Godfrey, Christopher; Sullivan, Matthew J.; St John, James A.; Ulett, Glen C.; Ekberg, Jenny A. K. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus agalactiae causes neonatal meningitis and can also infect the adult central nervous system (CNS). S. agalactiae can cross the blood-brain barrier but may also reach the CNS via other paths. Several species of bacteria can directly invade the CNS via the olfactory and trigeminal nerves, which extend between the nasal cavity and brain and injury to the nasal epithelium can increase the risk/severity of infection. Preterm birth is associated with increased risk of S. agalactiae infection and with nasogastric tube feeding. The tubes, also used in adults, can cause nasal injuries and be contaminated with bacteria, including S. agalactiae. We here investigated whether S. agalactiae could invade the CNS after intranasal inoculation in mice. S. agalactiae rapidly infected the olfactory nerve and brain. Epithelial injury led to increased bacterial load in these tissues, as well as trigeminal nerve infection. S. agalactiae infected and survived intracellularly in cultured olfactory/trigeminal nerve- and brain-derived glia, resulting in cytokine production, with some differences between glial types. We also found that the S. agalactiae capsule significantly altered cytokine and chemokine responses and affected intracellular survival in trigeminal glia. In summary, this study shows that S. agalactiae can infect the CNS via the nose-to-brain path with increased load after epithelial injury, and that the bacteria can survive in glia.